Mediterranean diet during pregnancy and infant neurodevelopment: A prospective birth cohort study - Dai, Fei-cai; Wang, Peng; Li, Qiong; Zhang, Lei; Yu, Li-jun; Wu, Lin; Tao, Rui-xue; Zhu, Peng (Frontiers in Nutrition, 2023)
Background Embryonic neural development is associated with intrauterine nutritional status. However, few cohort studies estimated the relationship between maternal dietary patterns during pregnancy and offspring's early neurodevelopment. Objective To examine the impact of the Mediterranean diet (MD) during pregnancy on infant neurodevelopment, including the potential mediating role of cord blood metabolites. Methods Among 1,471 mother–child pairs in a prospective birth cohort study in Hefei, China, we investigated the associations between maternal MD score [calculated based on a validated food frequency questionnaire (FFQ)] and child neurodevelopment at infancy [assessed using Ages and Stages Questionnaires, Third Edition (ASQ-3)]. The cord blood metabolic markers (including C-peptide, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, total cholesterol, and triglycerides) were measured. Results The MD score was negatively associated with communication domain developmental delays in infants [relative risk (RR) with 95% CI: 0.34 (0.16, 0.72)]. Compared with girls, boys born from mothers with lower MD scores during pregnancy were inclined to the failure of the communication domain [RRs with 95% CI for boys: 0.34 (0.14, 0.84); for girls: 0.26 (0.06, 1.18)]. Mediation analysis showed that the association between the maternal MD score and failure of communication domain mediated by C-peptide was 19.4% in boys but not in girls. Conclusion Adhering to the MD during pregnancy was associated with a decreased risk of poor neurodevelopment, possibly mediated by lower levels of cord blood C-peptide.